2021
DOI: 10.1007/s10620-021-07007-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Morbidity and Mortality in COVID-19 Patients with Liver Injury

Abstract: Background There is a high prevalence of liver injury (LI) in patients with coronavirus disease 2019 (COVID-19); however, few large-scale studies assessing risk factors and clinical outcomes in these patients have been done. Aims To evaluate the risk factors and clinical outcomes associated with LI in a large inpatient cohort of COVID-19 patients. Methods Adult patients with COVID-19 between March 1 and April 30, 2020, were included. LI was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Interestingly, one previous study from Brazil has also reported much lower frequencies of AST and ALT elevations ( 24 ), but the authors only took those with levels of double the upper limit into account, which are less commonly seen in COVID-19. Indeed, most patients with COVID-19 in the present study, and several other reports had mild abnormalities of AST and/or ALT ( 2 , 4 , 5 , 11 , 14 , 19 , 25 ). The preponderance of abnormal levels of AST over ALT has been reported in several studies ( 4 , 5 , 19 , 22 , 25 ), particularly from the United States ( 14 - 16 , 20 , 26 , 27 ).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Interestingly, one previous study from Brazil has also reported much lower frequencies of AST and ALT elevations ( 24 ), but the authors only took those with levels of double the upper limit into account, which are less commonly seen in COVID-19. Indeed, most patients with COVID-19 in the present study, and several other reports had mild abnormalities of AST and/or ALT ( 2 , 4 , 5 , 11 , 14 , 19 , 25 ). The preponderance of abnormal levels of AST over ALT has been reported in several studies ( 4 , 5 , 19 , 22 , 25 ), particularly from the United States ( 14 - 16 , 20 , 26 , 27 ).…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, most patients with COVID-19 in the present study, and several other reports had mild abnormalities of AST and/or ALT ( 2 , 4 , 5 , 11 , 14 , 19 , 25 ). The preponderance of abnormal levels of AST over ALT has been reported in several studies ( 4 , 5 , 19 , 22 , 25 ), particularly from the United States ( 14 - 16 , 20 , 26 , 27 ). Some studies have reported a parallel increase of ALT and AST suggesting that this concordance may reflect a pattern of liver injury ( 22 ), which could be induced by different mechanisms including drug-induced, aggravation of previous CLD or cholangiocyte and/or endothelial cell dysfunction due to a cytokine storm ( 1 , 2 , 28 , 29 ).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations